2020
DOI: 10.1002/lpor.202000027
|View full text |Cite
|
Sign up to set email alerts
|

A Lead‐Free All‐Inorganic Metal Halide with Near‐Unity Green Luminescence

Abstract: As the increasing demand of lighting display technology, environmentallyfriendly, economic light-emitting materials with high performance are required. Herein, a novel solution-processed, highly emissive copper chloride compound -Cs 3 Cu 2 Cl 5 is reported. The crystal structure determined by the Rietveld refinement of the powder X-ray diffraction patterns shows that the corner-sharing tetrahedral Cu-Cl chains are surrounded by Cs + cations, yielding a one-dimensional structure at molecular level. The all-inor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 38 publications
2
49
0
Order By: Relevance
“…The Rietveld refinement of the powder XRD pattern indicated that Cs 3 Cu 2 Cl 5 adopts space group Cmcm ( a = 15.449[5] Å, b = 8.7562[3] Å, and c = 8.6814[3] Å) (see Tables S8–S10, Supporting Information), which is different from the I and Br analogs ( Pnma ), as shown in Figure 1d,e. [ 21–23 ] For the Cs 3 Cu 2 Cl 5 , each Cu + ion has been coordinated with three Cl − ions and adopted a near‐planar configuration. Through Cl corner sharing, two [CuCl 3 ] 2− units formed an isolated folded dimer [Cu 2 Cl 5 ] 3− with a 75.51° face angle.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The Rietveld refinement of the powder XRD pattern indicated that Cs 3 Cu 2 Cl 5 adopts space group Cmcm ( a = 15.449[5] Å, b = 8.7562[3] Å, and c = 8.6814[3] Å) (see Tables S8–S10, Supporting Information), which is different from the I and Br analogs ( Pnma ), as shown in Figure 1d,e. [ 21–23 ] For the Cs 3 Cu 2 Cl 5 , each Cu + ion has been coordinated with three Cl − ions and adopted a near‐planar configuration. Through Cl corner sharing, two [CuCl 3 ] 2− units formed an isolated folded dimer [Cu 2 Cl 5 ] 3− with a 75.51° face angle.…”
Section: Figurementioning
confidence: 99%
“…Notably, the localized holes, not the electrons, play a crucial role for STE emission, which is substantiated by the observance of distinct flat valence bands for all the efficient copper(I) halide emitters, such as Cs 3 Cu 2 I 5 (0D), Cs 3 Cu 2 Cl 5 (0D/quasi‐1D), Cs 5 Cu 3 Cl 6 I 2 (1D), CsCu 2 Cl 3 (1D), and Rb 2 CuCl 3 (1D). [ 9,15,22,29 ]…”
Section: Figurementioning
confidence: 99%
“…The optical detector was a SPT counting module. 25 The emitting ratios described by the number of probed over shot photons were obtained. All experiments were performed at room temperature except EPR.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, the concentration of chloride ion cannot be too high due to the intrinsic lattice instability. 33 The lattice expansion with increased Mn 2+ concentration can be assigned to the larger ion radius of Mn 2+ . 34 When doping concentration increases to 25%, the diffraction peak shifts back to a higher degree, indicating the saturation of Mn 2+ and lattice instability at high doping concentration, which will lead to poor optical properties undoubtedly.…”
Section: Main Textmentioning
confidence: 99%